Keeping communities at the centre of efforts to eliminate lymphatic filariasis: learning from the past to reach a future free of lymphatic filariasis. (22nd December 2020) - Krentel, Alison; Gyapong, Margaret; McFarland, Deborah A; Ogundahunsi, Olumide; Titaley, Christiana R; Addiss, David G
Abstract: Since the launch of the Global Programme to Eliminate Lymphatic Filariasis (GPELF) in 2000, more than 910 million people have received preventive chemotherapy for lymphatic filariasis (LF) and many thousands have received care for chronic manifestations of the disease. To achieve this, millions of community drug distributors (CDDs), community members and health personnel have worked together each year to ensure that at-risk communities receive preventive chemotherapy through mass drug administration (MDA). The successes of 20 y of partnership with communities is celebrated, including the application of community-directed treatment, the use of CDDs and integration with other platforms to improve community access to healthcare. Important challenges facing the GPELF moving forward towards 2030 relate to global demographic, financing and programmatic changes. New innovations in research and practice present opportunities to encourage further community partnership to achieve the elimination of LF as a public health problem. We stress the critical need for community ownership in the current Covid-19 pandemic, to counter concerns in relaunching MDA programmes for LF.